Sonophotocatalytic degradation of sulfadiazine by integration of microfibrillated carboxymethyl cellulose with Zn-Cu-Mg mixed metal hydroxide/g-C3N4 composite - Gholami, Peyman; Khataee, Alireza; Vahid, Behrouz; Karimi, Afzal; Golizadeh, Mortaza; Ritala, Mikko (Elsevier, 2020)
This research aimed to prepare a recoverable sonophotocatalyst, in which microfibrillated carboxymethyl cellulose (MFC) acted as the Zn-Cu-Mg-mixed metal hydroxide/graphitic carbon nitride (MMH/g-C3N4) carrier. The characteristics of bare and composite sonophotocatalysts were analyzed by the XRD, FT-IR, BET, DRS, PL and FE-SEM equipped with the EDX mapping. The performance of prepared composites (MMH/g-C3N4@MFC) with various weight ratios of the MMH/g-C3N4 was studied for the sonophotocatalytic degradation of sulfadiazine (SDZ) as the model emerging contaminant. 93% of SDZ was degraded using the most effective catalyst (MMH/gC(3)N(4)@MFC3) with 15% weight ratio of the MMH/g-C3N4 under the desired operating conditions including solution pH of 6.5, SDZ concentration of 0.15 mM and ultrasonic power of 300 W. The MMH addition to the gC(3)N(4) structure increased the separation of charge carriers generated via the visible light or ultrasound irradiations. Moreover, the MMH/g-C3N4 was dispersed uniformly on the MFC and consequently, more active sites were available to form reactive oxygen species (ROS), compared to powder form. Hydroxyl radicals ((OH)-O-center dot) were determined as the main ROS in the SDZ degradation by performing a series of scavenging experiments. Less than 10% decrease in the degradation efficiency of SDZ was observed during five subsequent experiments, which indicated the proper retention of the MMH/g-C3N4 particles in the MFC. The adequate mineralization of SDZ (83% decrease in chemical oxygen demand (COD)) was obtained after 200 min of treatment. Eventually, ten degradation intermediates were identified by the GC-MS analysis and a plausible degradation mechanism for the contaminant was proposed.
Keywords: Antibiotic degradation; Composite; Graphitic carbon nitride; Microfibrillated carboxymethyl cellulose; Mixed metal hydroxide; Sonophotocatalysis